Can speckle tracking of right ventricle add value for evaluation of asthma severity in children? - Ahmed Mohammad Abbas; Hany Hussein Mousa; Reda Biomy Bastawesy; Osama Elagamy (Journal of the Pakistan Medical Association, 2023)
Objective: To investigate myocardial deformation by tracking speckles along with evaluation of cardiac function using conventional and tissue Doppler imaging. Method: The case-control study was conducted at Kafrelsheikh University Hospital, Egypt, from September 2019 to May 2022, and comprised asthmatic children and healthy controls matched for age and gender. After taking family history of asthma, assessments were made for bronchial asthma treatment and severity. Clinical examination and pulmonary function tests were performed along with tissue Doppler imaging and speckle tracking. Global left ventricular and right ventricular strains were measured. Data was analysed using SPSS 22. Results: Of the 120 subjects, 60(50%) were cases; 33(55%) males and 27(45%) females with mean age 9.4±2.91 years. The remaining 60(50%) were controls; 34(56.7%) males and 26(43.3%) females with mean age 9.7±2.99 years (p>0.05). Among the cases, 36(60%) had moderate severity and 24(40%) had mild asthma. Family history was positive in 11(18.3%) cases and negative in 49(81.7%). There was no significant difference in terms of conventional echocardiography between the groups (p>0.05). There was impairment in right ventricular diastolic function in the cases, with lateral tricuspid E` velocity significantly lower (p<0.05) and isovolumetric relaxation time significantly higher than the controls (p=0.001). There was impairment of systolic function of the right ventricle in the cases compared to the controls (p=0.001). Right ventricular peak longitudinal systolic stress cut-off value distinguishing the controls from the cases was -20.4 with sensitivity 85% and specificity 63%. The cut-off value distinguishing mild from moderate asthmatic cases was -19.8 with sensitivity 83% and specificity 91%. Conclusion: Speckle tracking echocardiography could detect very early subtle right ventricular systolic dysfunction. Right ventricle dysfunction worsened with the severity of asthma. Keywords: Hypertension, Pulmonary, Echocardiography, Respiratory, Asthma, Hypoxia.